The Problem of Potestative Conditions in Transactions - I. V. Popov (Сибирское юридическое обозрение, 2014)
The article deals with the problem connected with the possibility of the parties to include into the civil law contract some suspensive or cancelling conditions which depend on the will of one of the parties. The author produces proofs of scientists on this issue and illustrates with the help of examples from judicial practice the contradictoriness of the grounds related to the question under study. The author proposes to include into the RF Civil code the norm admitting the freedom of potestative conditions usage by the privies in civil law.